Associations Between Low-Household Income and First-Generation Status With College Student Belonging, Mental Health, and Well-Being. Issue 3 (June 2023) - Kreniske, Philip; Mellins, Claude A.; Shea, Eileen; Walsh, Kate; Wall, Melanie; Santelli, John S.; Reardon, Leigh; Khan, Shamus; Hwei, Tse; Hirsch, Jennifer S.
Entering college is recognized as a developmental milestone. Completing college is difficult, however, and students who are first-generation (FG) or low-income (LI) or both (FGLI) encounter unique challenges. In secondary analysis of data from a population-based survey ( N =1671 undergraduates) at two interconnected highly-selective institutions of higher education, we examined belonging, mental health, and well-being comparing the overall student body to FG, LI, and FGLI students. Most FG, LI, and FGLI students reported a strong sense of belonging, few mental health symptoms, and good general health and well-being. Compared to the overall student body, FG, LI and FGLI students reported lower levels of perceived family support, worse sleep quality, and worked more hours for pay; FG and FGLI students reported higher symptoms of depression; LI and FGLI reported less hazardous drinking. Interventions and programmatic changes at the institutional level are needed to build campuses where students of all backgrounds can thrive.